2018
DOI: 10.1002/anie.201802087
|View full text |Cite
|
Sign up to set email alerts
|

The N‐Methylpyrrolidone (NMP) Effect in Iron‐Catalyzed Cross‐Coupling with Simple Ferric Salts and MeMgBr

Abstract: The use of N-methylpyrrolidone (NMP) as a co-solvent in ferric salt catalyzed cross-coupling reactions is crucial for achieving the highly selective, preparative scale formation of cross-coupled product in reactions utilizing alkyl Grignard reagents. Despite the critical importance of NMP, the molecular level effect of NMP on in situ formed and reactive iron species that enables effective catalysis remains undefined. Herein, we report the isolation and characterization of a novel trimethyliron(II) ferrate spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 30 publications
(32 reference statements)
10
65
0
3
Order By: Relevance
“…At present, this catalytic system represents the catalyst of choice for the vast majority of iron‐catalyzed cross‐couplings in both academic and industrial settings . Mechanistic studies showed that NMP forms O‐coordinated catalytically active octahedral complexes of iron(II) ,. We were delighted to find that addition of NMP delivered the C4‐alkylated product in excellent 92% yield (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…At present, this catalytic system represents the catalyst of choice for the vast majority of iron‐catalyzed cross‐couplings in both academic and industrial settings . Mechanistic studies showed that NMP forms O‐coordinated catalytically active octahedral complexes of iron(II) ,. We were delighted to find that addition of NMP delivered the C4‐alkylated product in excellent 92% yield (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of structurally related yet more labile σ‐alkyl ferrates by Neidig and co‐workers constituted a milestone achievement in the mechanistic elucidation of Fe‐catalyzed cross‐couplings (Scheme , bottom). Reactions of FeX 3 (X=Cl, acac) with alkylmagnesium bromides (methyl, ethyl) in THF/ N ‐methyl‐2‐pyrrolidinone (NMP) under conditions very similar to those of cross‐couplings afforded the tridentate ferrates [Mg(nmp) 6 ][FeR 3 ] 2 (R=Me: 7 ; R=Et: 8 ) in very high spectroscopic yields . Indeed, both ferrates underwent quantitative cross‐coupling with alkenyl bromide; 8 also readily reacted with 4‐chlorobenzoate (Scheme ) .…”
Section: Methodsmentioning
confidence: 99%
“…Die Isolierung von strukturell verwandten, aber labileren σ‐Alkylferraten durch Neidig und Mitarbeiter stellte einen Meilenstein in der mechanistischen Aufklärung von Fe‐katalysierten Kreuzkupplungen dar (Schema , unten). Reaktionen von FeX 3 (X=Cl, acac) mit Alkylmagnesiumbromiden (Methyl, Ethyl) in THF/ N ‐Methyl‐2‐pyrrolidinon (NMP) unter Bedingungen sehr ähnlich wie bei Kreuzkupplungen lieferten die dreizähnigen Ferrate [Mg(nmp) 6 ][FeR 3 ] 2 (R=Me: 7 ; R=Et: 8 ) in sehr hohen spektroskopischen Ausbeuten . Tatsächlich gingen beide Ferrate eine quantitative Kreuzkupplung mit Alkenylbromid ein; 8 reagierte auch bereitwillig mit 4‐Chlorbenzoat (Schema ) .…”
Section: Methodsunclassified
“…In früheren Studien fanden Cahiez et al., dass NMP die unerwünschte β‐H‐Eliminierung in Fe‐katalysierten Kreuzkupplungen mit höheren Alkyl‐Grignard‐Reagenzien unterdrückt . Diese Beobachtung kann nun als eine effektive Gegenion‐Koordination interpretiert werden, welche die Bildung katalytisch aktiver monomerer Ferrate ermöglicht . Tatsächlich waren die Ethylferrate 8 und 10 inert gegenüber β‐H‐Eliminierung, was in voller Übereinstimmung mit zahlreichen Literaturberichten über Fe‐katalysierte Alkylkupplungen steht…”
Section: Methodsunclassified